The role of carbon catalyst coatings in the electrochemical water splitting reaction - William J. V. Townsend; Diego López-Alcalá; Matthew A. Bird; Jack W. Jordan; Graham A. Rance; Johannes Biskupek; Ute Kaiser; José J. Baldoví; Darren A. Walsh; Lee R. Johnson; Andrei N. Khlobystov; Graham N. Newton (Nature Communications)
Abstract Designing inexpensive, sustainable, and high-performance oxygen-evolution reaction (OER) electrocatalysts is one of the largest obstacles hindering the development of new electrolyzers. Carbon-coated metal/metal oxide (nano)particles have been used in such applications, but the role played by the carbon coatings is poorly understood. Here, we use a carbon-coated catalyst comprising metal-oxide nanoparticles encapsulated within single-walled carbon nanotubes (SWNTs), to study the effects of carbon coatings on catalytic performance. Electrolyte access to the encapsulated metal oxides is shut off by plugging the SWNT ends with size-matched fullerenes. Our results reveal that the catalytic activity of the composite rivals that of the metal oxide, despite the fact that the metal oxides cannot access the bulk electrolyte. Moreover, the rate-determining step (RDS) of the OER matches that measured at empty SWNTs, indicating that electrocatalysis occurs on the carbon surface. Synergism between the encapsulated metal oxide and carbon coating was explored using electrochemical Raman spectroscopy and computational analysis, revealing that charge transfer from the carbon host to the metal oxide is key to the high electrocatalytic activity of carbon in this system; decreasing electron density on the carbon surface facilitates binding of –OH, accelerating the rate of the OER on the carbon surface.